Strategi Pemasaran Bank Syariah Dengan Digital Marketing (Studi Kasus : Bank BSI Kc Ciputat) - Dewi, Sinta; Fasa, Muhammad Iqbal; Suharto, Prof (Prodi Perbankan Syariah Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2022)
Sharia Bank is a bank that is run with the principles of Islamic law in its operational activities. In Indonesia itself, there have been many Islamic banks that have been around for a long time, but Indonesian people tend to use conventional banks as their means of banking transactions because they think that conventional banks are more efficient and easier to transact. For this reason, a number of Islamic banks immediately carry out marketing plans in which they introduce products in Islamic banks to customers in order to meet the level of customer satisfaction in transactions. Many marketing concepts are used by a number of Islamic banks as long as they continue to carry out the company's ethical identity, for that a number of Islamic banks implement a number of marketing strategies to attract customers to switch to Islamic banks. With the enactment of Law No. 21 of 2008 concerning Islamic Banking, it can strengthen the position of Islamic banking. Then, supported by the MUI fatwa regarding several contract products, it also strengthened the position of Islamic banking. With the issuance of the fatwa haram bank interest by the MUI, it will change the paradigm of society and will increase the number of sharia bank customers. Meanwhile, Bank Indonesia as the monetary authority must give more flexibility to Islamic banking so that it can be affordable throughout Indonesia. In this global era, technology is growing so that it affects developments in marketing at Islamic banks using digital marketing. There are various ways of marketing in the digital era such as websites, email, or other social media such as Tik-tok, Instagram and others.